Lines of Flight - Richard A. Carter (Media + Environment)
Can the act of gliding perform also as an act of writing? The sweeping movements of a glider aircraft through the sky already inscribe a range of transient, circular traces—an asemic script that is written at the intersection between wind, wing, and piloting ability. Can these gestures provide the basis for more complex acts of inscription, in which human and atmospheric agencies combine to parse the vital experience of flight into poetry? Lines of Flight is a series of volumetric poems depicting the entanglements of wind, wing, and flying technique that constitute the airborne encounter. This creative-critical piece visualises a number of tracked glider flights in three dimensions, and uses this tracking data to generate a lexical poem along the route taken. As a form of inscription enabled through a multitude of intersecting airborne forces and volumes, this project enacts a creative-critical exploration of what writing the air can tell us about human relationships with the more-than-human world.